Differential gene expression of some lignocellulolytic enzymes in Aspergillus niger biofilms - Villena, Gretty K. (2008)
A preliminary evaluation of transcriptional gene expression in Aspergillus niger ATCC 10864 biofilms developed on polyester cloth was carried out. The expression analysis of genes encoding some lignocellulolytic enzymes and some regulatory genes by means of RT-PCR showed that eng1, eglC, exo, eglA, eglB and xynB genes are differentially expressed in biofilm fermentation either time-related or through the production of more than a transcript as compared to A. niger grown in submerged fermentation. Likewise, the regulatory genes xlnR and creA showed time-related expression patterns that were different in both fermentation systems. Results attained in this work contribute with an initial molecular evidence of differential gene expression as well as differential gene regulation patterns in fungal biofilms that may be related to cell adhesion.